Photoresponsive Surface Molecularly Imprinted Polymers for the Detection of Profenofos in Tomato and Mangosteen - Chen, Mei-jun; Yang, Hai-lin; Si, Ya-min; Tang, Qian; Chow, Cheuk-fai; Gong, Cheng-bin (Frontiers in Chemistry, 2020)
As a moderately toxic organophosphorus pesticide, profenofos (PFF) is widely used in agricultural practice, resulting in the accumulation of a high amount of PFF in agricultural products and the environment. This will inevitably damage our health. Therefore, it is important to establish a convenient and sensitive method for the detection of PFF. This paper reports a photoresponsive surface-imprinted polymer based on poly(styrene-co-methyl acrylic acid) (PS-co-PMAA@PSMIPs) for the detection of PFF by using carboxyl-capped polystyrene microspheres (PS-co-PMAA), PFF, 4-((4-(methacryloyloxy)phenyl)diazenyl) benzoic acid, and triethanolamine trimethacrylate as the substrate, template, functional monomer, and cross-linker, respectively. PS-co-PMAA@PSMIP shows good photoresponsive properties in DMSO/H2O (3:1, v/v). Its photoisomerization rate constant exhibits a good linear relationship with PFF concentration in the range of 0~15 μmol/L. PS-co-PMAA@PSMIP was applied for the determination of PFF in spiked tomato and mangosteen with good recoveries ranging in 94.4–102.4%.